Effect of Low-Dose, Long-Term Roxithromycin on Airway Inflammation and Remodeling of Stable Noncystic Fibrosis Bronchiectasis - Liu, Jifeng; Zhong, Xiaoning; He, Zhiyi; Wei, Lianghong; Zheng, Xiaozhen; Zhang, Jianquan; Bai, Jing; Zhong, Wei; Zhong, Dengjun (Mediators of Inflammation, 2014)
Background. Noncystic fibrosis bronchiectasis (NCFB) is characterized by airway expansion and recurrent acute exacerbations. Macrolide has been shown to exhibit anti-inflammatory effects in some chronic airway diseases. Objective. To assess the efficacy of roxithromycin on airway inflammation and remodeling in patients with NCFB under steady state. Methods. The study involved an open-label design in 52 eligible Chinese patients with NCFB, who were assigned to control (receiving no treatment) and roxithromycin (receiving 150 mg/day for 6 months) groups. At baseline and 6 months, the inflammatory markers such as interleukin- (IL-)8, neutrophil elastase (NE), matrix metalloproteinase- (MMP)9, hyaluronidase (HA), and type IV collagen in sputum were measured, along with the detection of dilated bronchus by throat computed tomography scan, and assessed the exacerbation. Results. Forty-three patients completed the study. The neutrophil in the sputum was decreased in roxithromycin group compared with control (P<0.05). IL-8, NE, MMP-9, HA, and type IV collagen in sputum were also decreased in roxithromycin group compared with the control group (all P<0.01). Airway thickness of dilated bronchus and exacerbation were reduced in roxithromycin group compared with the control (all P<0.05). Conclusions. Roxithromycin can reduce airway inflammation and airway thickness of dilated bronchus in patients with NCFB.